STRATEGI PENGEMBANGAN POTENSI DESA SENDANGSARI, PAJANGAN, KABUPATEN BANTUL MELALUI ANALISIS SWOT - Sukhemi, Sukhemi; Sumarmi, Saptaningsih; Siswanta, Lilik (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- The purpose of this study was to determine the potential, problems, and formulation of the Sendangsari village development strategy, Pajangan sub-district, Bantul District, Yogyakarta Special Region. Design/methodology/approach- This type of research is qualitative with a descriptive approach. Data sources used are primary data and secondary data. Key people as primary data sources are village officials and village community leaders. Secondary data were obtained from Disdukcapil, Central Bureau of Statistics, village office. The research method for analyzing research data uses descriptive analysis and SWOT analysis.Findings- The results of the study found that many village potentials could be developed with the right strategies and programs. The potential of natural, historical, and cultural tourism can be developed in Sendangsari village.Implications- Development. The resulting development program has implications for the economic recovery of the Sendangsari village community. Increased human resources in the form of providing training will be able to increase human resource competencies.Keywords: Rural Potencies, Village Issues, SWOT, Development Strategy.